Voluntary intake of captive psittacines fed mixed diets of seeds and extruded feed - Saldanha, André; Machado, Rodrigo Girata; Fernandes, Barbara Decker; Oliveira, Júlia Caroline de; Carvalho, Gabriela Amorim; Moreno, Tatiane Brandão; Rocha, Chayane da (Archives of Veterinary Science, 2023)
This study aimed to determine the feed, nutrient, and energy intake of three different small/medium psittacine species fed four different feeds based on three different types of seeds (canary seeds - Phalaris canariensis, millet seeds - Panicum miliaceum, and sunflower seeds - Helianthus annuus) and extruded feed. For this study, 21 individuals of each species (21 rose-ringed parakeets - Psitaculla krameri; 21 lovebirds - Agapornis spp.; 21 cockatiels – Nymphicus hollandicus) were individually housed in cages for the evaluation of voluntary feed, nutrient, and energy intake. Rose-ringed parakeets preferentially (P < 0.001) consumed sunflower seeds, while lovebirds, selected millet seeds over extruded feed without sunflower seeds (P < 0.013). When sunflower seed was not provided, all bird species selected millet seeds over extruded feed (rose-ringed P = 0.003; cockatiels P = 0.004; lovebirds P = 0.013). Selective feeding on sunflower seeds resulted in a higher intake of fat, protein, and gross energy. Low calcium intake (lower than 0.3%) and an imbalanced calcium-to-phosphorus ratio were observed in diets where extruded feed was not consistently consumed. The energy intake for the rose-ringed birds was 28.8 kcal/day, and 17,4 kcal/day for cockatiels, and lovebirds. These values exceeded the recommended maintenance energy requirement when experimental diets containing sunflower seeds and exclusively extruded feed were offered. Psittacine feed intake varies according to the type of feed and among species, and this selective feeding behavior can result in nutritional imbalances, causing chronic disorders.